Middle Ordovician Upwelling-Related Ironstone of North Wales: Coated Grains, Ocean Chemistry, and Biological Evolution - Dunn, Sarah K.; Pufahl, Peir K.; Murphy, J. Brendan; Lokier, Stephen W. (Frontiers in Earth Science, 2021)
Middle Ordovician phosphatic ironstone of the Welsh Basin provides new insight into the paleoenvironmental significance of ironstone and Ordovician ocean chemistry. Deposition occurred in a back-arc basin along the southern margin of Avalonia as the Rheic Ocean opened to the south. Ironstone is interpreted to have accumulated as part of an aggradational parasequence on a storm-dominated shelf with coastal upwelling. This parasequence has a laminated pyritic mudstone base that grades upward into variably bioturbated mudstone and coated grain-rich, intraclastic ironstone, which is overlain in turn by cross-stratified grainstone composed entirely of coated Fe grains. A coarser clastic parasequence composed of more proximal lithofacies rests conformably above and suggests the contact between the two parasequences is a maximum flooding surface marking the onset of highstand conditions. Lithofacies associations suggest that sustained coastal upwelling created a wedge of nutrient-rich, ferruginous seawater on the middle shelf that stimulated high surface ocean productivities. Large, coated Fe grains (granule size) composed of discontinuous and concentric carbonate fluorapatite, hematite, and chamosite cortical layers record fluctuations in pore water Eh that are interpreted to have been related to changes in upwelling intensity and intermittent storm reworking of the seafloor. Coated grain-rich facies are enriched in the redox-sensitive trace metals V, Cr, and Zn, corroborating sedimentologic evidence for a hydrothermal rather than terrestrial origin of Fe. Results support an emerging model for Ordovician ironstone underpinned by the development of ferruginous bottom water that was periodically tapped by coastal upwelling. Expanding, semi-restricted seaways such as the Rheic Ocean were ideal locations for the ponding of this anoxic, hydrothermally enriched seawater, especially during the early Paleozoic when the deep ocean was variably and inconsistently oxygenated. The coincidence of ironstone depositional episodes with graptolite diversification events suggests that, in addition to Fe, the sustained supply of upwelling-related P may have driven the radiation of some planktonic ecosystems during the Great Ordovician Biodiversification Event. Concomitant minor extinctions of benthic trilobites occurred as these ferruginous waters impinged on the shelf.